Competition warm-up strategies in sub-elite and elite flat-water sprint kayak athletes - Hogan, C.; Binnie, M. J.; Doyle, M.; Peeling, P. (Journal of Sports Sciences, 2021)
This study compared warm-up strategies employed by sub-elite and world-class elite sprint kayak athletes, evaluating their impact on subsequent race performance. Forty-seven (n = 33 male, n = 14 female) athletes competing at a National Sprint Kayak Championships had Global Navigation Satellite System devices fitted to their kayak to measure speed, distance and stroke rate during the on-water warm-up before racing (OWWU), and during racing. The OWWU total duration, average/peak speeds and stroke rates, and the time spent in speed-zones classified based upon athletes` relative race-pace (low-to-moderate, moderate-to-high, and race-specific) were compared between events, sexes, and athlete standard. The relationship of these variables to subsequent race performance, expressed as a percentage of the best time-to-completion for each event (%racebest), was also examined. Women spent greater OWWU time at moderate-to-high and race-specific speeds compared to men prior to 200-m and 500-m races (P =.001). Sub-elite men reported greater total OWWU duration for 200-m and 500-m (P =.025), but not for 1000-m races (P >.05) compared to elite men. Finally, %racebest had large inverse correlations to OWWU peak speed for men`s 200-m (r = -.53), and average stroke rate for women`s 500-m races (r = -.50). This study provides valuable insight for competition warm-up routines based upon data from an elite athlete population.